Inhomogeneous Distribution of Regional Myocardial Work Efficiency Predicts Early Left Ventricular Remodeling After Acute Anterior Myocardial Infarction Treated With Primary Percutaneous Intervention - Wang, Wei; Zhao, Hang; Wan, Fang; Shen, Xue-dong; Ding, Song; Pu, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed to investigate the hypothesis that specific pattern of myocardial work (MW) distribution in patients with acute anterior ST-segment elevation myocardial infarction (STEMI) could provide prognostic value for predicting left ventricular (LV) remodeling. Methods: Ninety-eight first anterior wall STEMI patients treated with primary percutaneous coronary intervention [85 men (86.7%), mean age: 58±12 years] were enrolled. Transthoracic echocardiography was preformed 24-72 hours after angioplasty and during 3-month follow-up. MW was estimated from left ventricular pressure–strain loop derived from speckle tracking echocardiography and simultaneous non-invasive brachial artery cuff pressure. The primary endpoint was early LV remodeling, defined as an increase in LV end-diastolic volume ≥ 20% compared with baseline at 3 months after STEMI. Major adverse cardiac events and combined clinical outcomes were recorded. Results: LV remodeling was present in 32 patients (33%), who exhibited lower global and culprit-regional work index (WI), constructive work (CW), work efficiency (WE), and specifically, greater differences of WE (delta-WE) and CW (delta-CW) between the culprit and non-culprit region than those without LV remodeling both at acute phase and follow-up (all P < 0.0125). During follow-up, all global and regional WI, CW and WE were improved (P < 0.0125 compared with baseline), with less improvement in patients with LV remodeling. In multivariate analysis, baseline delta-WE (odds ratio 2.304; 95% CI, 1.093-4.856, P = 0.028) and peak troponin I level (odds ratio, 1.035; 95%CI, 1.008-1.063, P = 0.010) were independently associated with early LV remodeling. Patients with greater delta-WE at baseline was associated with higher incidence of heart failure and combined clinical outcomes during follow-up. Conclusion: After reperfused acute anterior STEMI, patients with LV remodeling presented with more inhomogeneous MW distribution. The absolute difference of WE between culprit and non-culprit territory at the acute phase is an independent predictor for early LV remodeling. Clinical Trial Registration: www.ClinicalTrials.gov, identifier: NCT05107102